A perspective on tools for assessing the building sector’s greenhouse gas emissions and beyond - Fiona Greer; Paul Raftery; Gail Brager; Arpad Horvath (Environmental Research: Infrastructure and Sustainability, 2023)
Increasing impacts from anthropogenic climate change, coupled with the rising need to provide safe and healthy buildings in which people can live, work, and play, necessitates methods and tools for decarbonizing the building sector. Governments, industry, and others are interested in assessing both the embodied and operational greenhouse gas (GHG) emissions of buildings. Stakeholders have embraced whole building life-cycle assessment (WBLCA) as a framework for quantifying the life-cycle impacts of buildings, from raw material extraction to the building’s end of life. The purpose of this perspective is to offer an analysis on prominently used WBLCA tools, focusing on how well the tools are suited for assessing the embodied and operational GHG emissions from all phases of a building’s life cycle, and to suggest recommendations for improving the tools. Existing WBLCA tools can provide a detailed assessment of most materials used in the building’s core and shell but lack the capability to quantify impacts accurately and comprehensively from all building systems as well as from the construction, transportation, operation, and end-of-life phases. Suggested short term improvements for the tools include: (1) increased standardization among tools and environmental product declarations (EPDs) to allow for detailed comparison among different material options earlier in the design process; (2) incorporation of verified, local-manufacturer EPDs for all building materials, components, and systems and of specific on-site conditions; and (3) integration of tradeoffs between embodied and operational design decisions. We need to move beyond the prevailing approach of using WBLCA tools to select building materials that have the lowest embodied footprint. Future WBLCA tools need to be able to assess, in detail, how different design, construction, transportation, operation, and end-of-life decisions for a building not only affect GHG emissions, but other key sustainability goals including resilience to climate change, environmental justice, and human health of local communities.